RACE TO THE EUROZONE: WHY LATVIA JOINED BEFORE LITHUANIA - Markevičiūtė, Anastazija; Kuokštis, Vytautas (Baltic Journal of Political Science, 2017)
Why did Latvia join the Eurozone in 2014, while Lithuania only acceded a year later? The two countries’ diverging experiences are surprising. Latvia suffered a more pronounced economic crisis from 2008 to 2010, which created greater euro adoption challenges in terms of meeting fiscal criteria. This article argues that, while the willingness to adopt the euro increased in both countries during and after the crisis, the will to seek euro adoption was stronger, clearer and more consistent in Latvia than in Lithuania. In examining this divergence, we argue that relying on aggregate economic costs and benefits, identity considerations, geopolitical considerations, societal support, and interest group preferences does not produce a satisfactory explanation of fluctuations in these countries’ willingness to adopt the euro. Instead, we propose that changes in this willingness can be traced to domestic political processes, such as the timing and results of elections and the magnitude of the economic crisis’s impact.